Simulating effects of drainage design parameters on optimum crop yield using drainmod (2011)
"Agricultural water management system aims to provide crop water requirement to sustain optimum yield. Some of the factors influencing optimum crop yield are drainage design parameters in water logged soils. Hence, the impact of drainage design parameters on optimum crop yield was examined, field experimentation was for 12 weeks which includes land preparation, planting to maturity of Corchorus olitorius ('Ewedu') on a poorly drained sandy loam of National Horticultural Research Institute, Ibadan 'fadama' field. Hourly rainfall and daily minimum and maximum temperature data for 32 years (1963-1994) for Ibadan was obtained from Nigerian Meteorological Station as DRAINMOD input data. Aluminum drainage pipes at 110cm drain spacing, 60cm drain depth and effective radius of 5.08cm was installed. Depth from drain to restrictive layer was 204.3cm while drainage coefficient was 1.3cm/day. Drainage system parameters, such as grain spacing, drain depth, effective drain pipe radius were varied and effects on crop yield observed. Field evaluation was conducted at 60cm and 110cm drain depth and spacing respectively, and relative crop yield of 36.39% was attained at 40cm, 45cm, and 55cm drain depth, corresponding to 120cm, 115cm and 105cm spacing respectively when drain depth was varied with drain spacing at constant drain pipe effective radius it was concluded that if land availability is limiting and there is availability of cheap labour typical of developing countries drain depth of 55cm, and drain spacing of 105cm and drain pipe effective radius of 2.54cm (i.e 1 inch pipe) corresponds with the optimum yield of Corchorus olitorius. However, shorter drain spacing requires more drainage pipes and land reformation; hence increase in production cost. "